2022
DOI: 10.3233/cbm-210201
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics model of 18F-FDG PET/CT imaging for predicting disease-free survival of early-stage uterine cervical squamous cancer

Abstract: BACKGROUND: To explore an effective predictive model based on PET/CT radiomics for the prognosis of early-stage uterine cervical squamous cancer. METHODS: Preoperative PET/CT data were collected from 201 uterine cervical squamous cancer patients with stage IB-IIA disease (FIGO 2009) who underwent radical surgery between 2010 and 2015. The tumor regions were manually segmented, and 1318 radiomic features were extracted. First, model-based univariate analysis was performed to exclude features with small correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In their study, Calles-Sastre et al [ 35 ] found the pre-treatment TLG and MTV to be independent prognostic factors for OS and recurrence-free survival in patients with advanced cervical cancer patients who underwent definitive CCRT; these variables were better than the widely-used parameter, SUV max . The performance of the radiomics model in predicting PFS could be improved by incorporating MTV or TLG, as selected using univariate and multivariate Cox analysis [ 36 , 37 ]. However, none of the parameters, including SUV max , SUV mean , MTV, and TLG have been used for clinical decision-making in primary cervical tumors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Calles-Sastre et al [ 35 ] found the pre-treatment TLG and MTV to be independent prognostic factors for OS and recurrence-free survival in patients with advanced cervical cancer patients who underwent definitive CCRT; these variables were better than the widely-used parameter, SUV max . The performance of the radiomics model in predicting PFS could be improved by incorporating MTV or TLG, as selected using univariate and multivariate Cox analysis [ 36 , 37 ]. However, none of the parameters, including SUV max , SUV mean , MTV, and TLG have been used for clinical decision-making in primary cervical tumors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated the potential utility of radiology in predicting survival of cervical cancer patients, with reported accuracy higher than that of traditional clinical factors [31][32][33][34]. However, the sample sizes of these studies were relatively small and did not focus on early cervical cancer cases treated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated the potential utility of radiology in predicting survival of cervical cancer patients, with reported accuracy higher than that of traditional clinical factors [ 32 35 ]. However, the sample sizes of these studies were relatively small and did not focus on early cervical cancer cases treated with surgery.…”
Section: Discussionmentioning
confidence: 99%